Assessment of Mandibular Trauma Sustained in Motorcycle Accidents at Liaquat University Hospital Hyderabad - Mahavosh Qazi, Muhammad Shahzad, Mavina Munir, Bhavesh Maheshwari, Syed Zafar Abbas, Muhammad Aqeel Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Motorcycle accidents regularly impact the maxillofacial structures, with the mandible being one of the most usually shattered bones. Helmets have been found to have a preventive effect in avoiding maxillofacial injuries, although their impact on the likelihood of mandibular fractures is unknown. Objective: To assess the pattern of mandibular trauma among the motorcycle accidents reported at Liaquat university hospital Hyderabad. Subject and Methods: A total of 150 patients having mandibular fracture were selected. Patient’s data including age, gender, use or no use of a protective helmet at the time of trauma, type and site of fracture, speed limit and collision pattern weren recorded on a prescribed design Performa. Diagnosis of the trauma was carried out on the basis of clinical and radiographic evaluation (PA view of face, Orthopantomogram). Results: Males were predominantly affected as compared to females. Mean age in male was 29.5 and in females 33. 96 subjects were not using helmets during trauma. Most of the patients were having compound fracture. Collision with car was mostly seen as etiology. Parasymhysis with condyle was most common site involved followed by isolated parasymphysis and symphysis. Conclusion: To reduce the amount of face injuries in such incidents, educational programmes, defensive driving, and the usage of appropriate helmets are required.